An Analysis of the Dairy Supply Chain in Inner Mongolia - Lu, Dan (2013)
In the past 20 years, people have started to pay attention to the health issues with the focus on the food hygiene and safety. Therefore, the liquid milk and dairy products have gradually become the essential food in daily life. However, many quality problems occurred during the expansion of the dairy industry. With an interest in the dairy industry in Inner Mongolia of China, its predominant geological location and long history of dairy culture lead to Inner Mongolia developed into the centre of dairy production. In order to achieve the further development, it is necessary to identify its advantages and disadvantages that might influence the dairy industry. UK is the third largest milk producer in the EU; therefore, such an outstanding performance should rely on the advanced management methods implemented and support its sustainable development. Those valuable experiences and advanced management techniques could make a considerable dedication to the Inner Mongolian dairy industry if applied correctly. This dissertation reviews the relevant literature on the supply chain management, chilled food supply chain and dairy supply chain. An explanation of the case study method provides will follow. The Supply Chain Operation Reference (SCOR) model implements in the process of data collection and analysis. Some identification of the difference between the dairy supply chain in the UK and Inner Mongolia could be relevant factors to promote the further development of Inner Mongolia dairy industry. It concludes that the identifications could lead to some recommendations to enhance its strength and cover the shortages, from the perspective of cold V chain construction, information management and the concept of lean and sustainable development. This dissertation may be of interest to the dairy producer in Inner Mongolia, which intend to improve the supply chain system. For the purpose of developing local dairy industry, the related organizations might also be interested.